Answer:
m=7
Remainder =4
If q=1 then r=3 or r=-1.
If q=2 then r=3.
They are probably looking for q=1 and r=3 because the other combinations were used earlier in the problem.
Step-by-step explanation:
Let's assume the remainders left when doing P divided by (x-1) and P divided by (2x+3) is R.
By remainder theorem we have that:
P(1)=R
P(-3/2)=R
![P(1)=2(1)^3+m(1)^2-5](https://tex.z-dn.net/?f=P%281%29%3D2%281%29%5E3%2Bm%281%29%5E2-5)
![=2+m-5=m-3](https://tex.z-dn.net/?f=%3D2%2Bm-5%3Dm-3)
![P(\frac{-3}{2})=2(\frac{-3}{2})^3+m(\frac{-3}{2})^2-5](https://tex.z-dn.net/?f=P%28%5Cfrac%7B-3%7D%7B2%7D%29%3D2%28%5Cfrac%7B-3%7D%7B2%7D%29%5E3%2Bm%28%5Cfrac%7B-3%7D%7B2%7D%29%5E2-5)
![=2(\frac{-27}{8})+m(\frac{9}{4})-5](https://tex.z-dn.net/?f=%3D2%28%5Cfrac%7B-27%7D%7B8%7D%29%2Bm%28%5Cfrac%7B9%7D%7B4%7D%29-5)
![=-\frac{27}{4}+\frac{9m}{4}-5](https://tex.z-dn.net/?f=%3D-%5Cfrac%7B27%7D%7B4%7D%2B%5Cfrac%7B9m%7D%7B4%7D-5)
![=\frac{-27+9m-20}{4}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B-27%2B9m-20%7D%7B4%7D)
![=\frac{9m-47}{4}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B9m-47%7D%7B4%7D)
Both of these are equal to R.
![m-3=R](https://tex.z-dn.net/?f=m-3%3DR)
![\frac{9m-47}{4}=R](https://tex.z-dn.net/?f=%5Cfrac%7B9m-47%7D%7B4%7D%3DR)
I'm going to substitute second R which is (9m-47)/4 in place of first R.
![m-3=\frac{9m-47}{4}](https://tex.z-dn.net/?f=m-3%3D%5Cfrac%7B9m-47%7D%7B4%7D)
Multiply both sides by 4:
![4(m-3)=9m-47](https://tex.z-dn.net/?f=4%28m-3%29%3D9m-47)
Distribute:
![4m-12=9m-47](https://tex.z-dn.net/?f=4m-12%3D9m-47)
Subtract 4m on both sides:
![-12=5m-47](https://tex.z-dn.net/?f=-12%3D5m-47)
Add 47 on both sides:
![-12+47=5m](https://tex.z-dn.net/?f=-12%2B47%3D5m)
Simplify left hand side:
![35=5m](https://tex.z-dn.net/?f=35%3D5m)
Divide both sides by 5:
![\frac{35}{5}=m](https://tex.z-dn.net/?f=%5Cfrac%7B35%7D%7B5%7D%3Dm)
![7=m](https://tex.z-dn.net/?f=7%3Dm)
So the value for m is 7.
![P(x)=2x^3+7x^2-5](https://tex.z-dn.net/?f=P%28x%29%3D2x%5E3%2B7x%5E2-5)
What is the remainder when dividing P by (x-1) or (2x+3)?
Well recall that we said m-3=R which means r=m-3=7-3=4.
So the remainder is 4 when dividing P by (x-1) or (2x+3).
Now P divided by (qx+r) will also give the same remainder R=4.
So by remainder theorem we have that P(-r/q)=4.
Let's plug this in:
![P(\frac{-r}{q})=2(\frac{-r}{q})^3+m(\frac{-r}{q})^2-5](https://tex.z-dn.net/?f=P%28%5Cfrac%7B-r%7D%7Bq%7D%29%3D2%28%5Cfrac%7B-r%7D%7Bq%7D%29%5E3%2Bm%28%5Cfrac%7B-r%7D%7Bq%7D%29%5E2-5)
Let x=-r/q
This is equal to 4 so we have this equation:
Subtract 4 on both sides:
![2u^3+7u^2-9=0](https://tex.z-dn.net/?f=2u%5E3%2B7u%5E2-9%3D0)
I see one obvious solution of 1.
I seen this because I see 2+7-9 is 0.
u=1 would do that.
Let's see if we can find any other real solutions.
Dividing:
1 | 2 7 0 -9
| 2 9 9
-----------------------
2 9 9 0
This gives us the quadratic equation to solve:
![2x^2+9x+9=0](https://tex.z-dn.net/?f=2x%5E2%2B9x%2B9%3D0)
Compare this to ![ax^2+bx+c=0](https://tex.z-dn.net/?f=ax%5E2%2Bbx%2Bc%3D0)
![a=2](https://tex.z-dn.net/?f=a%3D2)
![b=9](https://tex.z-dn.net/?f=b%3D9)
![c=9](https://tex.z-dn.net/?f=c%3D9)
Since the coefficient of
is not 1, we have to find two numbers that multiply to be
and add up to be
.
Those numbers are 6 and 3 because
while
.
So we are going to replace
or
with
then factor by grouping:
![2x^2+6x+3x+9=0](https://tex.z-dn.net/?f=2x%5E2%2B6x%2B3x%2B9%3D0)
![(2x^2+6x)+(3x+9)=0](https://tex.z-dn.net/?f=%282x%5E2%2B6x%29%2B%283x%2B9%29%3D0)
![2x(x+3)+3(x+3)=0](https://tex.z-dn.net/?f=2x%28x%2B3%29%2B3%28x%2B3%29%3D0)
![(x+3)(2x+3)=0](https://tex.z-dn.net/?f=%28x%2B3%29%282x%2B3%29%3D0)
This means x+3=0 or 2x+3=0.
We need to solve both of these:
x+3=0
Subtract 3 on both sides:
x=-3
----
2x+3=0
Subtract 3 on both sides:
2x=-3
Divide both sides by 2:
x=-3/2
So the solutions to P(x)=4:
![x \in \{-3,\frac{-3}{2},1\}](https://tex.z-dn.net/?f=x%20%5Cin%20%5C%7B-3%2C%5Cfrac%7B-3%7D%7B2%7D%2C1%5C%7D)
If x=-3 is a solution then (x+3) is a factor that you can divide P by to get remainder 4.
If x=-3/2 is a solution then (2x+3) is a factor that you can divide P by to get remainder 4.
If x=1 is a solution then (x-1) is a factor that you can divide P by to get remainder 4.
Compare (qx+r) to (x+3); we see one possibility for (q,r)=(1,3).
Compare (qx+r) to (2x+3); we see another possibility is (q,r)=(2,3).
Compare (qx+r) to (x-1); we see another possibility is (q,r)=(1,-1).